Estetika Postmodernisme dalam Hĳab style - Linda Handayani; Gungun Gunardi; Nani Darmayanti (LP2M ISBI Bandung, 2014)
ABSTRACT Hĳab style is a new term in the fashion Muslim hĳab that marked novelty shapes. Since the ap- pearance of Hĳabers Community in 2010 , there were many changes in the form of veil that accom- panied the change of name became Hĳab style hĳab. Hĳab is initially mandatory Muslim clothing to cover nakedness . Novelty Hĳab style made it not only a practice of God command but also become part of fashion . Updates on the form that is often referred to as modernization pull analyzed in terms of aesthetics. Hĳab which used by designers founder Hĳabers Community becomes the object of this study. The method used in this study is a qualitative approach to the study of cultural and semiotic theory models Baudrillard. The signs were there in style hĳab as an aesthetic representation of post- modernism will be described. As cultural products that spread through the mass media, Hĳab style became popular and developed following the postmodern aesthetic principled form follows fun. Keywords: Hĳab style, aestetics, postmodernism, consumerism, fashion ABSTRAK Hĳab style merupakan istilah baru dalam fashion muslimah yang menandai kebaruan bentuk jilbab. Sejak kemunculan Hĳabers Community tahun 2010, terjadi banyak perubahan bentuk pada jilbab yang diiringi perubahan nama dari jilbab menjadi Hĳab style. Jilbab pada awalnya adalah pakaian wajib muslimah untuk menutup aurat. Kebaruan Hĳab style mem- buatnya tidak hanya menjadi praktik menutup aurat tapi juga menjadi bagian dari fashion. Pembaruan pada bentuk yang kerap disebut sebagai modernisasi menarik dianalisis dari sisi estetika. Hĳab yang digunakan oleh desainer-desainer pendiri Hĳabers Community menjadi objek penelitian ini. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan kajian budaya dan teori semiotik model Baudrillard. Tanda-tanda yang ter- dapat dalam Hĳab style sebagai representasi dari estetika postmodernisme akan diuraikan. Sebagai produk budaya yang menyebar melalui media massa, Hĳab style menjadi popular dan berkembang mengikuti estetika postmodernisme yang berprinsip form follows fun. Kata kunci: Hĳab style, estetika, postmodernisme, konsumerisme, fashion